2022
DOI: 10.1039/d1py01643a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced SET to access olefin-acrylate copolymers

Abstract: The advantageous material properties that arise from combining non-polar olefin monomers with activated vinyl monomers have led to considerable progress in the development of viable copolymerization strategies. However, unfavorable reactivity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…40,41 The phthalimide-containing repeating unit was also found to be effective in providing a main-chain radical species through single-electron transfer-induced reductive decarboxylation, which could be utilized for degradable olefin-acrylate copolymer. 42,43 To introduce the trigger-responsive site in the pendent chain should lead to retaining the properties as the polymer material, such as thermal-and photo-stability, compared to the labile bond directly on the backbone. In this study, therefore, novel pendant-responsive comonomers were designed for the synthesis of interlocking degradable vinyl polymers, which can trigger the backbone scission through main-chain radical species.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 The phthalimide-containing repeating unit was also found to be effective in providing a main-chain radical species through single-electron transfer-induced reductive decarboxylation, which could be utilized for degradable olefin-acrylate copolymer. 42,43 To introduce the trigger-responsive site in the pendent chain should lead to retaining the properties as the polymer material, such as thermal-and photo-stability, compared to the labile bond directly on the backbone. In this study, therefore, novel pendant-responsive comonomers were designed for the synthesis of interlocking degradable vinyl polymers, which can trigger the backbone scission through main-chain radical species.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] More recently, Sumerlin and co-workers published a similar method to synthesize polyolefins based on a different catalytic system. [11] But the scope of decarboxylation of polymeric materials is by far not only limited to the synthesis of polyolefins.…”
Section: Introductionmentioning
confidence: 99%
“…There have recently been numerous examples of decarboxylative radical cross-coupling small-molecule reactions utilizing N -(acyloxy)­phthalimide derivatives as single-electron transfer (SET) acceptors. Applying this class of transformation to polymer-based systems seems to be a promising and somewhat untapped avenue to expand the field of post-polymerization modification. , We and Theato et al have recently reported redox-active monomers containing N -(acyloxy)­phthalimide (NAP) moieties that possess the ability to function as latent backbone radicals. These phthalimide ester compounds are vinyl monomers capable of radical copolymerization and act as SET acceptors. SET from an inexpensive, organic photocatalyst SET donor (Eosin Y, EY) ,, to the NAP monomer units after incorporation into a polymer triggers the decarboxylative generation of a backbone radical which is then quenched with an H atom donor to afford olefin repeat units.…”
mentioning
confidence: 99%
“…In this case, the rate of β-scission was slow compared to the rate of coupling. In previous work it was shown that production of a backbone radical in copolymer 4 in the presence of an H atom donor yielded ethylene/acrylate copolymers, meaning that polymer coupling can be suppressed through the addition of a radical quenching species.…”
mentioning
confidence: 99%